Analysis of topological organization of chromatin during spermatogenesis in mouse testis - Narayan Gopeshwar; Raman Rajiva (Genetics and Molecular Biology, 2004)
Eukaryotic chromatin is organized as radial DNA loops with periodical attachments to an underlying nucleoskeleton known as nuclear matrix. This higher order chromatin organization is revealed upon high salt extraction of cells. To understand the sequential change in the functional organization of chromatin during spermatogenesis, we have analysed the higher order organization of chromatin in different testicular cell types and the epididymal sperm of laboratory mouse. The expansion and contraction of the nucleoid DNA following 2 M NaCl extraction was measured in a fluorescence microscope using ethidium bromide (2.5-200 mg/mL) as an intercalating dye to induce DNA positive supercoils. While the halo size varied among cell types (pachytene DNA most extended, round spermatid least), 5 mg/mL ethidium bromide (EtBr) removed maximum negative supercoils in all the cell types. At higher EtBr concentrations, maximum positive supercoiling occured in pachytene DNA loops. Consistent with this, the pachytene looped domains were maximally sensitive to DNase I, while the elongated spermatids and sperms were highly resistant. Our data suggest that pachytene DNA is in the most open chromatin conformation of all testicular cell types, while round spermatids show the most compact conformation in terms of EtBr intercalation.